Utilization of a central venous catheter insertion care bundle in Taiwan: A cross-sectional analysis of the National Health Insurance Research Database - Chung, Hui-Chun (Tzu Chi Med J, 2019)
OBJECTIVES: The objectives of this study are to explore medical care utilization associated with promoting the central venous catheter (CVC) care bundle plan using Taiwan's National Health Insurance Research Database (NHIRD). MATERIALS AND METHODS: We performed a cross-sectional, secondary analysis of the data from patients who were admitted to a medical center for the first time between July 1, 2010, and June 30, 2012, in the NHIRD. The control group was patients who were admitted at nine medical center hospitals that participated in the pilot plan, and the study group was patients who were admitted at other ten medical center hospitals that did not participate in the pilot plan, and the differences between groups were analyzed. RESULTS: After implementing the CVC care bundle, the average hospital stay decreased significantly (18.43 ± 12.96 vs. 15.49 ± 10.16, P < 0.05). In addition, the study group patients were clinically less likely to require antibiotics than the control group (odds ratio = 0.33, 95% confidence interval [CI] = [0.07, 1.71] vs. 0.62, 95% CI = [0.40, 0.96], P = 3768), and their medical expenses were lower (220, 618 ± 226, 419 vs. 208, 079 ± 193, 610, P > 05). Furthermore, the incidence rate of CVC-associated sepsis decreased from 12.59% to 5.66%. CONCLUSIONS: By implementing the CVC care bundle in clinical practice in accordance with national policies, medical utilization decreased, thereby considerably improving medical resource usage. These results confirmed that implementing the CVC care bundle possibly decreased medical utilization in clinical practice.